Modal control in the optimal shape control and the shape control research of a paraboloid antenna under different stimulations - Yao, Guo-Feng; Gao, Xue-Fei; Chen, Su-Huan (Smart materials and structures, 2005)
In this paper, a precise integration algorithm is introduced to deal with structural dynamics. Because the optimal shape control requests real-time control and the CPU time for computing feedback control is as short as possible, the modal control algorithm is given. The computing cost is less than that of the all state feedback control. Finally, the control effects of a paraboloid antenna under different stimulations are studied.